Painting in a State of Exception: New Figuration in Argentina, 1960-1965 - Frank, Patrick (University Press of Florida, 2016)
"Brings long overdue recognition and reevaluation to Nueva Figuración. Offers a contemporary reexamination of the artworks beyond that of Argentina's complex political history for a more global interpretation."--Carol Damian, author ofNeorealism and Contemporary Colombian Painting "Chronicles an important and little-known episode in the history of Argentine art and thoughtfully locates the movement within the complex cultural and political landscape of its time."--Abigail McEwen, University of Maryland, College Park Although it is one of Latin America's most significant postwar art movements, Nueva Figuración has long been overlooked in studies of modern art. In this first comprehensive examination of the movement, Patrick Frank explores the work of four artists at its heart--Jorge de la Vega, Luis Felipe Noé, Rómulo Macció, and Ernesto Deira--to demonstrate the importance of their work in the transnational development of modern art. The artists were responding directly to a difficult and chaotic period characterized by civil strife, frequent changes of government, and economic shocks. They broke new ground in Latin American art, not only in their technique, but also in the way they engaged the social, political, and cultural climate in an Argentina still recovering from the Perón years. Building on postwar expressionism by working with unprecedented urgency and abandon, they combined spontaneous techniques of abstraction with collage elements and figural subjects. Their works exercised a creative freedom that broke taboos about the role of the artist in society. Frank combines analyses of each artist's paintings with discussions of their social, political, and artistic contexts. He reveals the works' connections to literature, popular culture, and film, broadening our understanding of modern art in the early 1960s. Patrick Frank is the author of several books, includingLos Artistas del Pueblo: Prints and Workers' Culture in Buenos Aires, 1917-1935, and Posada's Broadsheets: Mexican Popular Imagery, 1890-1910."Brings long overdue recognition and reevaluation to Nueva Figuración. Offers a contemporary reexamination of the artworks beyond that of Argentina's complex political history for a more global interpretation."--Carol Damian, author ofNeorealism and Contemporary Colombian Painting "Chronicles an important and little-known episode in the history of Argentine art and thoughtfully locates the movement within the complex cultural and political landscape of its time."--Abigail McEwen, University of Maryland, College Park Although it is one of Latin America's most significant postwar art movements, Nueva Figuración has long been overlooked in studies of modern art. In this first comprehensive examination of the movement, Patrick Frank explores the work of four artists at its heart--Jorge de la Vega, Luis Felipe Noé, Rómulo Macció, and Ernesto Deira--to demonstrate the importance of their work in the transnational development of modern art. The artists were responding directly to a difficult and chaotic period characterized by civil strife, frequent changes of government, and economic shocks. They broke new ground in Latin American art, not only in their technique, but also in the way they engaged the social, political, and cultural climate in an Argentina still recovering from the Perón years. Building on postwar expressionism by working with unprecedented urgency and abandon, they combined spontaneous techniques of abstraction with collage elements and figural subjects. Their works exercised a creative freedom that broke taboos about the role of the artist in society. Frank combines analyses of each artist's paintings with discussions of their social, political, and artistic contexts. He reveals the works' connections to literature, popular culture, and film, broadening our understanding of modern art in the early 1960s. Patrick Frank is the author of several books, includingLos Artistas del Pueblo: Prints and Workers' Culture in Buenos Aires, 1917-1935, and Posada's Broadsheets: Mexican Popular Imagery, 1890-1910.